2015
DOI: 10.18632/oncotarget.4617
|View full text |Cite
|
Sign up to set email alerts
|

Local production of the chemokines CCL5 and CXCL10 attracts CD8+ T lymphocytes into esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a very common malignant tumor with poor prognosis in China. Chemokines secreted by tumors are pivotal for the accumulation of CD8+ T lymphocytes within malignant lesions in several types of cancers, but the exact mechanism underlying CD8+ T lymphocyte homing is still unknown in ESCC. In this study, we revealed that, compared with marginal tissues, the expression of both chemokine (C-C motif) ligand 5 (CCL5) and (C-X-C motif) ligand 10 (CXCL10) was upregulated in ESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 44 publications
4
76
0
Order By: Relevance
“…Further, knockdown of CCL5 in murine colorectal carcinoma cells delays tumor growth and decreases both Treg cell infiltration and CD8 ϩ T-cell apoptosis (65). In contrast, in human ESCC tissue samples, CCL5 is correlated with increased CD8 ϩ lymphocyte markers and a prolonged overall survival of patients (66). In this study, 4-MU decreased the Ccl5 mRNA expression in CAF co-cultures.…”
Section: Journal Of Biological Chemistry 4101mentioning
confidence: 51%
“…Further, knockdown of CCL5 in murine colorectal carcinoma cells delays tumor growth and decreases both Treg cell infiltration and CD8 ϩ T-cell apoptosis (65). In contrast, in human ESCC tissue samples, CCL5 is correlated with increased CD8 ϩ lymphocyte markers and a prolonged overall survival of patients (66). In this study, 4-MU decreased the Ccl5 mRNA expression in CAF co-cultures.…”
Section: Journal Of Biological Chemistry 4101mentioning
confidence: 51%
“…Nevertheless, 5-aza-induced local production of cytokines, including CCL5 (Fig. 3), which are known to attract T cells (53,54), suggests possibly beneficial, at least for some patients, combination of 5-aza with immunotherapy (anti-PD-L1/PD-1), as the number of tumor-infiltrating CD8 þ T cells was found to predict response to anti-PD-1/PD-L1…”
Section: -Azamentioning
confidence: 99%
“…Relatively recent studies have revealed that chemokines regulate the movement of a wide variety of immune cells including lymphocytes, NK cells, and DCs in both physiological and pathological conditions (79). These features mean that chemokines play crucial roles in immune responses.…”
Section: The Important Role Of Chemokines In Lung Carcinomamentioning
confidence: 99%